Implementation Of Ecoprint As An Environmentally Friendly Educational Media For The Children Of Alue Gadeng Dua Village - Mastura; Mutia Sumarni; Fajril Mubin; Uci Ardina; Widya Ramadani; Nurfauziah Farhana; Riza Ardiansyah; Rabithah Zulsa Matondang; Julia Santika; Sintha Agustin; Facrull Razi; Nabila Fatwa Amalia Isma; Khairunnisa Mardiyah; Intanna Mauliza (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2026)
The purpose of this service is to implement ecoprint as an environmentally friendly educational medium for children. The activity was held on August 16, 2025, located at the Alue Gadeng Dua Village Hall, Birem Bayeun District, East Aceh Regency. This activity involved 25 elementary school children as participants. The activity method uses an educational participatory approach that emphasizes the active involvement of participants in each stage of the activity. The evaluation was carried out through observation of children's enthusiasm, creativity and ability to make ecoprint works. The results of the activity showed that all participants were able to produce unique and creative ecoprint products. The impact of this service can be seen from the increase in children's active participation in environmentally friendly activities and the growing sense of responsibility in using natural resources wisely. Thus, ecoprint has proven to be effective as an environmentally friendly educational medium as well as a means of developing children's creativity at the elementary school level.